The Effect of B Share Market Reform on Volatility Spillovers and Changes in Correlation between Chinese A and B Shares - Chan, Felix; Da Veiga, Bernardo; Mcaleer, M. (Modelling and Simulation Society of Australia and New Zealand, 2005)
© MODSIM 2005 - International Congress on Modelling and Simulation: Advances and Applications for Management and Decision Making, Proceedings. All rights reserved. The aim of this paper is to investigate the effect of the Chinese B share market reform on the correlation and information transmission between A and B Shares issued in the Shanghai and Shenzen stock exchanges. Daily returns for the Shanghai A share index (SHA), Shanghai B share index (SHB), Shenzen A share index (SZA) and Shenzen B share index (SZB) are used for the period 6 October 1992 to 8 February 2005. The results suggest that the all pairs of correlations increase dramatically over the period analysed, but such increase begins well before the reforms to the B Share market.